A new importance assessment method for risk‐informed SSC categorization. (19th January 2018) - Jiaqun, Wang; Fang, Wang; Jin, Wang; Shanqi, Chen; Liqin, Hu; Yazhou, Li; Chun, Li
Summary: This paper proposed a new importance assessment method and new importance measure to perform risk‐informed system, structure, and components (SSCs) categorization task, regarding the dynamic of SSCs' importance measures caused by varied configurations in nuclear power plants (NPPs). The new method consists of 3 importance measures, Fussell Vesely, risk achievement worth, and return to service worth, and an integrated time ratio factor is introduced to get an SSCs ranking, which could handle more realistic configurations in NPP operation. The proposed method has been used in CANDU feedwater system SSCs categorization, supported by RiskA and RiskAngel software, and a different SSCs categorization result compared with NEI method was given. The difference of categorization result derived from 2 methods was discussed in this paper, and the effectiveness has been demonstrated by the NPP's real operation statistics. Abstract : We proposed a new method, return to service worth importance and an integrated time ratio factor for SSCs ranking, to perform risk‐informed system, structure, and components (SSCs) categorization. We applied this framework in CANDU feedwater system SSCs categorization and got a different SSCs categorization result compared with NEI method. We demonstrated more attention focus on the accuracy of SSCs categorization.